Why do students choose the option of the Open Syllabus in a conventional university? - Eugene Matusov (Dialogic Pedagogy)
The purpose of the presented mixed qualitative-quantitative research is to examine college students’ diverse reasons for choosing the Open Syllabus, which allows students in a conventional university to define their goals for education, curriculum, instruction, assessment, ways of learning, and so on—what traditionally constitutes “Self-Directed Education.” Most of those students articulated their interest in self-education, which consists of self-directed and responsive education.